Sanctioning of illegal and dangerous ruck cleanouts during the 2018 Super Rugby competition - Kraak, W.; Bam, J.; Kruger. S.; Henderson, S.; Josias, U.; Stokes, K. (Frontiers in Psychology, 2019)
Rugby is a high contact sport that results in many injuries. The majority of injuries at senior elite levels result from contact phases during match-play. It is estimated that 10% of all match injuries are associated with the ruck in professional and community rugby. Surveillance of legal and illegal ruck cleanouts and the sanctions imposed by the on-field referees will help identify whether referees are actually enforcing the law according to the laws of the game, which will consequently contribute to the creation and implementation of further injury prevention strategies. Players should play the game in accordance with the laws of the game and be mindful of their own safety and that of others. Coaches and trainers of the game have the responsibility to ensure that players are prepared in a manner that comply with the World Rugby (WR) laws of the game and safe practices. Laws and law amendments are fundamental to the development of sport and introduced for a variety of reasons. The aim of this study was to investigate the rate of sanctioning of illegal and dangerous ruck cleanouts during the 2018 Super Rugby competition by using Nacsport Basic+ video software; 120 round robin matches from the 2018 Super Rugby competition were coded and analyzed. The analysis of the intra reliability showed an almost perfect (>0.95) agreement between all the performance indicators. In total, 22,281 ruck cleanouts were coded of which 9% (n = 2111) were illegal ruck cleanouts and 93% were not sanctioned by the referees; 57% (1087 out of 1953) of the illegal ruck cleanouts not sanctioned by the referees were deemed dangerous. The majority of dangerous illegal ruck cleanouts not sanctioned by the referees were "shoulder charge" (88%, n = 280), "neck roll" (86%, n = 100), and "contact above the shoulder" (81%, n = 201). To aid injury prevention efforts in rugby, future research studies should investigate why on-field referees are not sanctioning all illegal and dangerous ruck cleanouts according to WR Laws of the Game.